2019
DOI: 10.1001/jamaophthalmol.2018.4484
|View full text |Cite
|
Sign up to set email alerts
|

Association of Disorganization of Retinal Inner Layers With Visual Acuity Response to Anti–Vascular Endothelial Growth Factor Therapy for Macular Edema Secondary to Retinal Vein Occlusion

Abstract: inner layers (DRIL) has demonstrated significant correlations with visual acuity (VA) in center-involved diabetic macular edema. In patients with retinal vein occlusion (RVO) and secondary macular edema, DRIL may be a useful biomarker in determining VA outcomes. OBJECTIVE To examine whether DRIL at baseline and after treatment is associated with VA in RVO. DESIGN, SETTING, AND PARTICIPANTSA retrospective review of records of 147 patients 18 years or older with treatment-naive branch RVO (BRVO), central RVO (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…Previous studies reported the close correlation in diabetic retinopathy between DRILs and macular capillary non-perfusion, detected by Fluorescein Angiography (FA). Furthermore, the presence of DRILs was associated with reduction of visual acuity in patients with DME or with resolved macular edema [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies reported the close correlation in diabetic retinopathy between DRILs and macular capillary non-perfusion, detected by Fluorescein Angiography (FA). Furthermore, the presence of DRILs was associated with reduction of visual acuity in patients with DME or with resolved macular edema [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…7 OCT has been used extensively in the investigation of RVO, including evaluating changes in central subfield thickness (CST), intraretinal and subretinal fluid (SRF), photoreceptor damage, ellipsoid zone (EZ) integrity, and disorganization of inner retinal layers (DRIL). [8][9][10][11] The EZ is 1 of 4 outer retinal hyperreflective bands. It is the second-most inner band just posterior to the external limiting membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors of RVO are known to include hypertension, systemic vascular disease, hyperlipidemia, pregnancy, oral contraceptive use, and hypercoagulability; however, the underlying pathogenesis of RVO remains unclear [3]. Interestingly, some studies have shown that local and systemic inflammation can induce both atherosclerosis and systemic hypercoagulability, which influence the development of ME secondary to RVO (RVO-ME) [4]. Several studies have shown that the levels of inflammatory factors (e.g., vascular endothelial growth factor [VEGF], interleukin-1β, and interleukin-6) are associated with the severity of ME [5].…”
Section: Introductionmentioning
confidence: 99%